Generación de un visor ambiental GIS WEB mediante ArcGIS Online free para el Campus Sur UPS - Pino Casignia, Sandra Paulina (2018)
The present study was carried out in the South Campus of the Salesian Polytechnic University located in the Quitumbe parish, Quito, province of Pichincha; with the purpose of generating an environmental viewer in ArcGIS Online free. For this purpose, it was required to take an orthophotography of the university campus with the use of a drone, the georeferencing and positioning of coordinates using GPS and total station, an action that helped to have greater accuracy when carrying out the work in countryside. Measures were taken of each of the spaces that are part of the south campus, as well as taking photographs of them. In addition, the AutoCAD survey was carried out of the spaces, which are part of the study area, thanks to which maps were generated in ArcGIS Desktop to finally add them to the ArcGIS Online computer tool, in which a map was generated web prior to the development of the environmental viewer that was obtained as a final product. In the same way, we proceeded to obtain all the information that could be georeferenced from the environmental monitoring part within the campus, this information was included and is now available in the viewer. As a final product of the investigation, the environmental viewer for the UPS South Campus was obtained, in which through a link and with Internet access it is possible to interactively navigate through the campus spaces, as well as visualize the environmental projects generated within the same. Keywords: viewer, ArcGIS Desktop, ArcGIS Online, AutoCAD, orthophotography, environmental projects, georeferencing.